2021
DOI: 10.1016/j.numecd.2020.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a risk factor for hospitalization in COronaVirus Disease-19 (COVID-19) patients: Analysis of the Tuscany regional database

Abstract: Background and Aims Aim of the present study is to determine the role of obesity as a risk factor for COronaVirus Disease-19 (COVID-19) hospitalization. Methods and Results This observational study was performed using Istituto Superiore di Sanità (ISS) Tuscany COVID-19 database by the Agenzia Regionale Sanità (ARS), including all COVID-19 cases registered until April 30 th , 2020, with reported information on chronic diseases. The principal ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…The finding that almost all study patients were overweight was not realized until conducting data analysis after the study had been completed (90 days after initial infusion for all study patients). The importance of this demographic is that obesity has emerged as a strong risk factor – perhaps second only to advanced age – for hospitalization among persons with acute COVID-19 [ 48 , 49 ]. Obesity, which is a component of the metabolic syndrome, is associated with the secretion of inflammatory adipokines [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that almost all study patients were overweight was not realized until conducting data analysis after the study had been completed (90 days after initial infusion for all study patients). The importance of this demographic is that obesity has emerged as a strong risk factor – perhaps second only to advanced age – for hospitalization among persons with acute COVID-19 [ 48 , 49 ]. Obesity, which is a component of the metabolic syndrome, is associated with the secretion of inflammatory adipokines [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of the data from the beginning of the pandemic, and partially confirmed later, revealed that the main risk factors for admission to intensive care with a fatal outcome were advanced age [ 6 ], male sex [ 7 ], smoking [ 8 ], obesity [ 9 , 10 ], hypertension [ 11 ], diabetes mellitus [ 12 , 13 , 14 , 15 ], lung disease [ 16 ], cancer [ 17 , 18 ], and cardiovascular disease [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to a collective loss of immune protection due to aging, which leads to cellular and molecular dysregulation of the innate immune system. However, as the pandemic progressed, it became clear that children were less severely affected, while only 2.5% of laboratory-confirmed cases of SARS-CoV-2 in children were reported to develop severe disease associated with a cytokine storm similar to that of secondary hemophagocytic lymphohistiocytosis (HLH) [ 10 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These patients need to be closely monitored and work in conjunction with a nutritionist to address the high body mass index [47]. Obesity as a risk factor for hospitalization during the COVID-19 pandemic was described by Bellini et al Using the Istituto Superiore di Sanita Tuscany COVID-19 database, the authors conducted an observational study evaluating the role of obesity as a risk factor hospitalization during the COVID-19 pandemic [48]. Of the 4481 subjects included in their cohort (36.9% aged over 70 years), 1907 (42.6%) were admitted to the hospital, and the association of obesity higher for hospitalized patients (OR: 2.99 (ci 95% 2.04-4.37)) [48].…”
Section: Impact Of Nutritional Statusmentioning
confidence: 99%
“…Obesity as a risk factor for hospitalization during the COVID-19 pandemic was described by Bellini et al Using the Istituto Superiore di Sanita Tuscany COVID-19 database, the authors conducted an observational study evaluating the role of obesity as a risk factor hospitalization during the COVID-19 pandemic [48]. Of the 4481 subjects included in their cohort (36.9% aged over 70 years), 1907 (42.6%) were admitted to the hospital, and the association of obesity higher for hospitalized patients (OR: 2.99 (ci 95% 2.04-4.37)) [48]. Based on the data mentioned earlier, BMI and nutrition status must be addressed in an outpatient setting upon hospital discharge.…”
Section: Impact Of Nutritional Statusmentioning
confidence: 99%